A flexible Mn0.5Ti2(PO4)3/C nanofiber film with superior cycling stability for potassium-ion batteries. Issue 47 (25th November 2021) - Dai, Jing; Su, Die; Yang, Jianping; Zhang, Wen; Wang, Qianfu; Liu, Li; Hu, Hai; Li, Huifang; Liu, Zhiming
Abstract : A flexible Mn0.5 Ti2 (PO4 )3 /C nanofiber film is first synthesized via electrospinning and applied to potassium-ion batteries as a self-standing anode, delivering exceptional mechanical flexibility and outstanding potassium-ion storage performance. Abstract : First-principles calculations indicate that Mn0.5 Ti2 (PO4 )3 is more suited to potassium-ion storage because of its lower energy gap than that of KTi2 (PO4 )3 . A flexible Mn0.5 Ti2 (PO4 )3 /C nanofiber film (F-MTP/C NFF) has been first synthesized via electrospinning and applied to potassium-ion batteries as a self-standing anode. An integral carbon conductive network, unique one-dimensional nanostructure, and exceptional mechanical flexibility give F-MTP/C NFF outstanding potassium-ion storage performance. Impressively, the self-standing F-MTP/C NFF electrode delivers a high specific capacity of 218 mA h g −1 at 0.02 A g −1 and shows ultra-long cycling stability of 2000 cycles at 1 A g −1 . This work may give a new insight into developing NASICON-type Ti-based materials as flexible electrodes for potassium-ion batteries.